2015
DOI: 10.4081/ijfs.2015.5358
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mislabelling in prepared fishery products in Southern Italy

Abstract: Fish authentication is a major concern not only for the prevention of commercial fraud, but also for the assessment of safety risks deriving from the undeclared introduction of potentially dangerous toxic or allergenic substances or environmentally damaging fish where endangered species are involved. Moreover, food authentication might affect the diet of certain groups of consumers, such as followers of religious practices. Considering the authentication of fish products is one of the key issues in food safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A small survey on the prevalence of mislabelling of fish fillets from markets and supermarkets in southern Italy was conducted in 2015 (Tantillo et al, 2015). Overall, 42.8 percent of fillets (sole, plaice, salmon and hake) were mislabelled, with 46.4 percent of plaice fillets being substituted with pangasius.…”
Section: Scale and Global Incidence Of Fish Fraudmentioning
confidence: 99%
“…A small survey on the prevalence of mislabelling of fish fillets from markets and supermarkets in southern Italy was conducted in 2015 (Tantillo et al, 2015). Overall, 42.8 percent of fillets (sole, plaice, salmon and hake) were mislabelled, with 46.4 percent of plaice fillets being substituted with pangasius.…”
Section: Scale and Global Incidence Of Fish Fraudmentioning
confidence: 99%
“…Several major studies in recent years have shown significant amounts of mislabelling (Oceana, 2016;Pardo, Jiménez and Pérez-Villarreal, 2016), affecting between 20 and 30 percent of fish sampled, from various parts of the marketing chain. More specific studies (among many) found mislabelling of 75 percent of red snapper in the United States of America (Marko et al, 2004); 41 percent of fish at retail level in Canada (Hanner et al, 2011); and 43 percent of fillets in southern Italy (Tantillo et al, 2015).…”
Section: Fish Fraudmentioning
confidence: 99%
“…The substitution of an animal or plant species of high commercial value with a cheaper, lower-quality one is a common fraud in the food industry, appearing in all branches from meat, seafood, and dairy products to food of plant origin, such as oils and juices. Accordingly, elevated mislabeling levels have been continuously published: 57% in processed meat products and 42.8% in fish fillets sold in Italy, 9,10 up to 35% in meat products sold in the United States, 11 24.4% in prawns and shrimps, 12 and up to 80% in dairy products. 13 Meat is particularly susceptible to fraudulent substitution by less valuable meat or meat coming from domestic animals.…”
Section: ■ Introductionmentioning
confidence: 99%